Lessons Learned From Google Glass: Telemedical Spark or Unfulfilled Promise?. (April 2016) - Yu, Jonathan; Ferniany, William; Guthrie, Barton; Parekh, Selene G.; Ponce, Brent
Importance . Wearable devices such as Google Glass could potentially be used in the health care setting to expand access and improve quality of care. Objective . This study aims to assess the demographics of Google Glass users in health care and determine the obstacles to using Google Glass by surveying those who are known to use the device. Design . A 48-question survey was designed to assess demographics of users, technological limitations of Google Glass, and obstacles to implementation of the device. Setting . The physicians surveyed worked in various fields of health care, with 50% of the respondents being surgeons. Participants . Potential participants were found using an Internet search for physicians using Google Glass in their practice. Main Outcome Measures . Outcome measures were divided into demographic information of users, technological limitations of the device, and administrative obstacles. Results . A 43.6% response rate was observed. The majority of users were male, assistant professors, in academic hospitals, and in the United States. Numerous technological limitations were observed by the majority, including device ergonomics, display location, video quality, and audio quality. Patient confidentiality and data security were the major concerns among administrative obstacles. Conclusions and Relevance . Despite the potential of Google Glass, numerous obstacles exist that limit its use in health care. While Google Glass has been discontinued, the results of this study may be used to guide future designs of wearable devices.